1999
DOI: 10.1046/j.1432-1327.1999.00476.x
|View full text |Cite
|
Sign up to set email alerts
|

Ionophoretic properties and mitochondrial effects of cereulide

Abstract: The emetic toxin of Bacillus cereus, found to cause immobilization of spermatozoa and swelling of their mitochondria, was purified and its structure found to be identical to the earlier known toxin cereulide. It increased the conductance in black-lipid membranes in KCl solutions in an ionophore-like manner. It formed adducts with K + , Na + , and NH 4 + but the conductance was highly selective for K + in relation to Na + and H + (three orders of magnitude). The increase in the kinetics of conductance indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
106
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(116 citation statements)
references
References 27 publications
5
106
0
1
Order By: Relevance
“…Cereulide causes swelling of the mitochondria of liver cells (16,25) and previous studies suggested that cereulide functions as an uncoupler to inhibit the mitochondrial respiratory chain (18,22). The present study also showed that cereulide uncoupled the mitochondrial respiratory chain and the energy transfer system similarly to uncouplers DNP and CCCP.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Cereulide causes swelling of the mitochondria of liver cells (16,25) and previous studies suggested that cereulide functions as an uncoupler to inhibit the mitochondrial respiratory chain (18,22). The present study also showed that cereulide uncoupled the mitochondrial respiratory chain and the energy transfer system similarly to uncouplers DNP and CCCP.…”
Section: Discussionsupporting
confidence: 75%
“…This method detects cereulide specifically as the chemical structure and is highly sensitive, but requires an expensive apparatus. Cereulide is a K ϩ ionophore and it has toxin activity when the K ϩ ion is held in the molecule (18). The proportion of K ϩ form in the preparation of cereulide varies according to the extraction method (21).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 10 3 to 10 4 CFU of Streptomyces g Ϫ1 were found in moisture-damaged indoor building materials (4,23), further increasing the airborne load of valinomycin. Valinomycin is highly hydrophobic (19) and therefore likely aerosolized. When inhaled, valinomycin is probably rapidly absorbed into the circulation.…”
Section: Discussionmentioning
confidence: 99%
“…MA147 were exposed to the substances for 24 h in broth culture. Cereulide was purified from Bacillus cereus F4810/72 as described previously (31). Fengycin and iturin were from Aibi Lipopeptides (Gembloux, Belgium), and surfactin was from Sigma-Aldrich (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The log K ow of amylosin is estimated to be 3 to 4 (43), making it less lipophilic than cereulide or paenilide, a toxin with higher hydrophobicity than cereulide that induces potassium efflux from mammalian cells and mitochondria and that is produced by Paenibacillus tundrae (29). This could explain why amylosin acts as a potassium efflux channel (2), leading to high levels of potassium ion release down the concentration gradient, instead of acting as a potassium ionophore and passing through the mitochondrial membrane as cereulide and paenilide do (29,31). Interestingly, cereulide has been reported to have no effect on the IL-1␤ production of monocytes (47), whereas amylosin was shown in the current study to have a strong activating effect on human macrophages, indicating that the potassium efflux-related activation of the NLRP3 inflammasome and subsequent cytokine secretion require a channel-based flow of potassium out of the cell.…”
Section: Figmentioning
confidence: 99%